REORIENTASI NASI BARINJI SEBAGAI KULINER KHAS TERNATE BERCITA RASA REMPAH - Rima Melati; Abdul Rahmat Mandea; Suratman Sudjud; Suryati Tjokrodiningrat; Kuad Suwarno; Zauzah Abdullatif; Ajrin Kailul (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
The Barinji Rice is a traditional culinary heritage of Ternate, rich in the flavor of spices and cultural significance. Its use remains limited to ritual offerings, placing local knowledge at risk of extinction. This community engagement initiative aims to reorient Barinji Rice as a signature culinary product that supports the branding of “Ternate, the City of Spices.” Through exploratory and experimental approaches, media outreach, exhibitions, and organoleptic testing, the activity revealed that Barinji Rice is now recognized and favored by 92% of respondents. This indicates its strong potential as a culinary business product, as well as a symbol of local cultural and economic identity.